2020
DOI: 10.1002/anie.201914397
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Polymer Dots with Dual‐Enhanced NIR‐IIa Fluorescence for Through‐Skull Mouse‐Brain Imaging

Abstract: Fluorescence probes in the NIR‐IIa region show drastically improved imaging owing to the reduced photon scattering and autofluorescence in biological tissues. Now, NIR‐IIa polymer dots (Pdots) are developed with a dual fluorescence enhancement mechanism. First, the aggregation induced emission of phenothiazine was used to reduce the nonradiative decay pathways of the polymers in condensed states. Second, fluorescence quenching was minimized by different levels of steric hindrance to further boost the fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
166
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(167 citation statements)
references
References 55 publications
0
166
1
Order By: Relevance
“…Recent studies demonstrated that fluorescence detection in the 1300-1400 nm region resulted in drastically improved SNR and penetration depth in deep-tissue imaging in vivo. [4,11] We explore the application of the fluorinated Pdots for through-scalp and through-skull imaging of mice brain. We compared the performance of m-PBTQ4F Pdots and ICG dye in the imaging of mouse cerebral vasculature.T he Pdots and ICG solution at the same injection dose (200 mgmL À1 ,100 mL) were administered into C57BL/6 mice through the tail vein.…”
Section: Quantitative Through-skull Imaging Of Brain Vasculaturementioning
confidence: 99%
“…Recent studies demonstrated that fluorescence detection in the 1300-1400 nm region resulted in drastically improved SNR and penetration depth in deep-tissue imaging in vivo. [4,11] We explore the application of the fluorinated Pdots for through-scalp and through-skull imaging of mice brain. We compared the performance of m-PBTQ4F Pdots and ICG dye in the imaging of mouse cerebral vasculature.T he Pdots and ICG solution at the same injection dose (200 mgmL À1 ,100 mL) were administered into C57BL/6 mice through the tail vein.…”
Section: Quantitative Through-skull Imaging Of Brain Vasculaturementioning
confidence: 99%
“…Moreover, in vivo blood vascular system images and lymphatic drainage mapping validated the long‐term stability and high spatial resolution of Pdots. Wu and the coworker proposed a dual enhancement strategy to enhance the semiconducting polymer‘s fluorescence mechanism in the NIR‐IIa region [18] . They exploited the AIE (aggregation‐induced emission) character of the phenothiazine (donor) unit to dwindle the nonradiative decay of the resulting polymers in the aggregated state and endowed bulky side groups to generate steric hindrance to produce the anti‐ACQ effect (Figure 4C).…”
Section: Deep‐tissue Fluorescence Imagingmentioning
confidence: 99%
“…These results demonstrate that the fluorinated Recent studies demonstrated that fluorescence detection in the 1300-1400 nm region resulted in drastically improved SNR and penetration depth in deep-tissue imaging in vivo. [4,11] We explore the application of the fluorinated Pdots for through-scalp and through-skull imaging of mice brain. We compared the performance of m-PBTQ4F Pdots and ICG dye in the imaging of mouse cerebral vasculature.T he Pdots and ICG solution at the same injection dose (200 mgmL À1 ,100 mL) were administered into C57BL/6 mice through the tail vein.…”
Section: Quantitative Through-skull Imaging Of Brain Vasculaturementioning
confidence: 99%